Breast cancer associated pathogenic variants among women 61 years and older with triple negative breast cancer. Issue 5 (June 2021) - Chávarri-Guerra, Yanin; Marcum, Catherine A.; Hendricks, Carolyn B.; Wilbur, Deborah; Cescon, Terrence; Hake, Christopher; Abugattas, Julio; Rodriguez, Yenni; Villarreal-Garza, Cynthia; Yang, Kai; Cervantes, Aleck; Sand, Sharon; et al.
Abstract: Women with triple negative breast cancer (TNBC) have a high prevalence of BRCA1 mutations, and current clinical guidelines recommend genetic testing for patients with TNBC aged ≤60 years. However, studies supporting this recommendation have included few older women with TNBC. Methods: Genetic testing results from women aged >60 years with TNBC enrolled in the Clinical Cancer Genomics Community Research Network (CCGCRN) registry were included in this analysis. Prevalence of breast cancer-associated pathogenic variants (PVs) was compared across age groups. Results: We identified 151 women with TNBC aged >60 years (median 65 years; SD 5.3). Of these, 130 (86%) underwent genetic testing, and a breast cancer–associated PV was identified in 16 (12.3%; 95% CI 7–19): BRCA1 ( n = 6), BRCA2 ( n = 5), PALB2 ( n = 2), ATM ( n = 1) and RAD51C (n = 2). We found no differences in the proportion of patients with close blood relatives with breast (≤50 years) or ovarian cancer (any age) between PV carriers (37.5%) and non-carriers (34.2%) ( p = 0.79). Among PV's carriers, the proportion of older women with a BRCA1 PV was lower when compared to younger women (37.5% vs 77.2%; p < 0.01). Conclusion: Breast cancer-associated PVs were found in an important proportion of women aged >60 years with TNBC undergoing genetic testing, including greater representation of BRCA2 . These results suggest that older women with TNBC should be offered genetic testing, and that their exclusion based on chronologic age alone may not be appropriate.